Organization of services for people with special needs at enterprises of the hotel and restaurant business (Economics and region, 2023)
The article explains the concepts of "disability", "person with a disability", "modern hospitality industry", "hotel and restaurant business". Based on the analysis of domestic scientific works, the analysis of factors and factors of interaction in the formation of the system of inclusive service at the enterprises of the hotel and restaurant business were identified: the influence on the characteristics of the enterprise of the hotel and restaurant business; influence on the level and quality of service provision, taking into account clients of the category of people with special needs (special menu, technical requirements for the entrance parts of the premises, presence of a call or quick response button, available medical, social and psychological services, which are included in the special service level of provision services); level of service regardless of the social status and characteristics of human needs; organization of the image in the field of service taking into account the inclusion of the individual. Two groups of factors are separated for the presence of the characteristics of the enterprise itself and the presence of the accommodation services parameter, which led to the development of the author's interpretation of the system of inclusive service at the enterprises of the hotel and restaurant business, which is divided into three main stages: the first is the provision of universal service for people with special needs (informational, medical , social, psychological, advisory, etc.); next (second) – access to all premises of the institution, including internal equipped rooms, halls, rooms, etc.; final (third) – availability of a special shuttle and an equipped parking space for people with special needs. Prospects for further research are related to the diagnosis and generalization of the obtained results regarding the disclosure of the significance and relevance of the existing features of the organization of services for people with special needs at the enterprises of the hotel and restaurant business.
Keywords: organization; inclusion; person with special needs; enterprise; hotel; restaurant; business; hotel-restaurant business